Valproate reopens critical-period learning of absolute pitch - Gervain, Judit; Vines, Bradley W.; Chen, Lawrence M.; Seo, Rubo J.; Hensch, Takao K.; Werker, Janet F.; Young, Allan H. (Frontiers in Systems Neuroscience, 2013)
Absolute pitch, the ability to identify or produce the pitch of a sound without a reference point, has a critical period, i.e. it can only be acquired early in life. However, research has shown that histone-deacetylase inhibitors (HDAC inhibitors) enable adult mice to establish perceptual preferences that are otherwise impossible to acquire after youth. In humans, we found that adult men who took valproate (a HDAC inhibitor) learned to identify pitch significantly better than those taking placebo – evidence that valproate facilitated critical-period learning in the adult human brain. Importantly, this result was not due to a general change in cognitive function, but rather a specific effect on a sensory task associated with a critical-period.